Characterization of complete chloroplast genome and phylogenetic analysis of sweet cherry Cerasus avium (L.) Moench (Prunoideae, Rosaceae). Issue 2 (3rd July 2018) - Chen, Tao; Hu, Guo-Ping; Wang, Yan; Chen, Qing; Wang, Lei; Zhang, Jing; Tang, Hao-Ru; Wang, Xiao-Rong
Abstract: Sweet cherry ( Cerasus avium (L.) Moench) belonging to family Rosaceae, is an important economical fruit crop worldwide. In this study, the complete chloroplast (cp) genome of sweet cherry was generated by De novo assembly with low coverage whole-genome sequencing data. The genome size was 157, 987 bp in length consisting of a typical quadripartite structure; a large single-copy region (LSC, 85, 975 bp), a small single-copy region (SSC, 19, 121 bp) and a pair of inverted repeat regions (IRs, 26, 445 bp each). A total of 115 genes were predicted including 82 protein-coding genes, 29 tRNA genes and four rRNA genes. Phylogenetic analysis based on 12 reported complete chloroplast genome indicated the monophyly of the genus Creasus including newly sequenced C. avium, which is conform to the traditional classification.